Amplitude‐integrated electroencephalography shows alterations in children born preterm displaying poor literacy precursor skills. (10th March 2019) - Burger, Christina; Biermayr, Marlene; Posod, Anna; Neubauer, Vera; Pupp Peglow, Ulrike; Kuenz, Katrin; Kiechl‐Kohlendorfer, Ursula; Griesmaier, Elke
Abstract: Aim: To assess whether amplitude‐integrated electroencephalography (aEEG) alterations in the newborn period are associated with poor precursor skills of literacy at five years of age in children born preterm. Methods: Between October 2007 and September 2011 248 preterm infants were eligible for the study at Innsbruck Medical University Hospital. aEEG was analysed for dominating background activity, calculation of the percentage of continuous activity, the Burdjalov scoring system, the minimum, mean and maximum amplitude. At the age of five years, we evaluated preterm born children by the Bielefelder screening (BISC) to assess for early diagnosis of reading problems and weak spelling and classified them as normal performers (n = 64) or poor performers (n = 20). Completion of testing was not possible for one infant. Results: The minimum amplitude was significantly lower in the poor BISC performance group as compared to the normal BISC performance group at postnatal week two. The percentage of continuous background activity was significantly higher in infants with normal BISC performance than in infants with poor BISC performance at postnatal week three. Conclusion: Children with poor developed precursor skills of literacy showed alterations in aEEG signals. The aEEG could be useful in further diagnosing preterm infants at risk for developmental complications.